Versatile Functional Energy Metabolism Platform Working From Research to Patient: An Integrated View of Cell Bioenergetics - Loric, Sylvain; Conti, Marc (Frontiers in Toxicology, 2022)
Technological development of high throughput large scale “omics” analysis of genes, transcripts, proteins, and metabolites, coupled or not to mathematic modelling into systems biology, has been thought to be the Holy Grail of drug and/or biomarker discovery. However, “omics” quantification low accuracy and precision induce propagation and accumulation of errors that can lead to misinterpretations, and then alter prediction efficiency. Moreover, as finding the presence of a protein does not augur its functionality, generation of even large number of motionless data, instead of dynamic functional ones, failed to show that system could be fully operational. Both impair early discovery of adverse effects and consequently generate late drug attrition. To address such issue, we describe complementary means that allows system functionality observation. We have developed a versatile functional metabolism platform that can measure quantitatively, in parallel, with a very high precision and accuracy, number of biological parameters like substrates or enzyme cascade activities in essential metabolism units (glycolysis, respiratory chain ATP production, oxidative stress...). From preclinical to clinical studies, it allows cell metabolism pathways fine tuning comparison. Applied to OXPHOS and/or oxidative stress, it allows discriminating compounds with acute toxic effects but, most importantly, those inducing low noise chronic ones.